Aneurysm of the lingual artery in a patient with fibromuscular dysplasia: A case report. Issue 1 (January 2022) - Yamamoto, Noriyuki; Yamaguchi, Satoshi; Nishikawa, Masaya; Ichimura, Norihisa; Ohara, Go; Hibi, Hideharu
Abstract: Lingual artery (LA) aneurysms are particularly rare, and pseudoaneurysms are associated with trauma, infection, and surgical intervention. LA aneurysms can be fatal if not recognised or treated; however, only a few cases of idiopathic LA aneurysms have been reported in the literature, all of which have been described as pseudoaneurysms. To address this knowledge gap in reporting a true LA aneurysm, here, we describe a 55-year-old woman with an idiopathic aneurysm of the lingual artery. The lesion was detected by another department on a computed tomographic angiography of the neck, which was performed as a post-aneurysmectomy evaluation of the right internal carotid artery. The embolisation failed twice, after which we performed an aneurysmectomy of the left atrium. A histopathological examination of the excised aneurysms revealed fibromuscular dysplasia (FMD). Thus, we believe that FMD may be a cause of external LA aneurysms. Our findings will be relevant for oral surgeons and physicians who may consider FMD as a differential diagnosis when treating multiple LA aneurysms.